Modulation of Listeria monocytogenes biofilm formation using small molecules and enzymes - Nguyen, Uyen (My University, 2014)
Inadequately disinfected food contact surfaces colonized by Listeria monocytogenes can come into contact with ready-to-eat food products causing cross-contamination and food-borne outbreaks. L. monocytogenes is tolerant of high salt, low temperatures and low pH, in part due to its ability to form biofilms, defined as communities of microorganisms that are surrounded by a self-produced extracellular polymeric substance that can adhere to surfaces. Biofilm formation is a complex process involving a series of poorly defined physiological changes that together lead to tolerance of disinfectants and antibiotics. To better understand the process of L. monocytogenes biofilm development, and to investigate ways in which colonization of surfaces might be prevented, we developed a microtiter biofilm assay suitable for high throughput screening. The assay was used to identify small molecules (protein kinase inhibitors and previously FDA-approved bioactive drugs) that modulate L. monocytogenes biofilm development. Of the subset of molecules with biofilm modulatory activities, we showed that select protein kinase inhibitors and β-lactams prevented or reduced biofilm formation (<50% of vehicle control) of L. monocytogenes lab strains and food isolates at micromolar concentrations. In other cases, specific β-lactams stimulated biofilm formation (>200% of vehicle control) at sub-minimal inhibitory concentrations. Characterization of the penicillin-binding protein targets of the β-lactams revealed that PBPD1, a low molecular weight D,D-carboxypeptidase, is targeted by non-stimulatory β-lactams. Stimulatory β-lactams did not increase biofilm formation of a pbpD1 mutant to the same extent as wild type. In addition to inhibiting biofilm formation, many β-lactams dispersed established biofilms, although not completely. However, targeting components of the EPS matrix with enzymes — specifically proteins, using proteinase K –completely blocked adhesion and removed established biofilms. Together, these findings demonstrate how molecules with different mechanisms of action can modulate biofilm formation and the potential for use of proteinase K in the food industry as an antibiofilm agent.